Foodborne diseases - Simjee, Shabbir (Infectious disease, 2007)
Presents a broad overview of the microbial pathogens and toxins associated with food borne illness while discussing pathogenicity, clinical epidemiology, diagnosis, and treatment. This book covers various bacterial pathogens, viruses, protozoans, and parasites, as well as microbial toxins